Coâproduction and biomass yield of amaranthus (Amaranthus hybridus ) and tilapia (Oreochromis niloticus) in gravelâbased substrate filter aquaponic - Taofik Ademola Babatunde; Kabir Ibrahim; Babangida Abdulkarim; Nasir Hassan Wagini; Samaâila Adamu Usman (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Aquaponics combine aquaculture with crop production in a mutual system. In this experiment, the growth of Amaranthus in aquaponics with tilapia fish was investigated. Method 500-liter water tanks containing tilapia fish at four initial stocking densities of 100, 150, 200, and 250 fish/m3 were used in triplicates, with a view to evaluate vegetable yields as influenced by fish biomass to water ratio. 1 g of Amaranthus seeds were sown in a 1 m2 planting trough, which contained gravel with a top layer of sandy soil. The pots were flooded with water from fish holdings by an aquarium pump. Results The germination rate of Amaranthus was not significantly different across the experimental setup (Pâ>â0.05). The growth rate of Amaranthus was significantly higher with increasing fish density (Pâ<â0.05). The average lowest and highest of shoots dry biomass yield recorded were 0.36 and 1.95 g/plant at 8 weeks after of sowing, and this corresponds to fish stocking densities of 100 and 250 fish/m3, respectively. A high positive correlation was found between the shoot dry biomass of Amaranthus and fish stocking density. The survival of tilapia fingerlings was not significant different, while the production levels were 5.62, 4.77, 4.57, and 4.00 kg/m2 in 100, 150, 200, and 250 fish/m3. Conclusion The growth of Amaranthus in this experiment demonstrated that the plant could effectively utilize the nitrogenous waste from fish tanks for biomass production, even at a higher concentration, while considerations for moderate fish density are only for fish health.